A study on the influence of workplace environment towards employees’ performance among private companies/ Nor Hafizah Nawi - Nawi, Nor Hafizah (Faculty of Business and Management, 2013)
The objective of this research is to study the influence of workplace environment towards employees’ performance in private companies in Kemaman Supply Base (KSB) area. The vision of Malaysia to become a developed nation by 2020. Thus, it needs a workforce that has high performance and capability to drive the nation’s growth and development. So, due to this challenge, performance of employees in private sector in this country is very important. The researcher wants to study based on the previous research in KSB area to look whether the workplace environment can influence employees’ performance. The respondent selected were 130 employees in eight private companies in KSB. 57.7 percent of respondents are male and 42.3 percent of respondents are female. Convenience sampling, which is non-probability sampling technique, was used in this study. Eight private companies were chosen for this research. Three independent variables (comfort level, office layout and level of interaction and distraction) were chosen in this study because those variables are the most relevant with the situation in KSB companies whereas the dependent variable is employees’ performance. All independent variables were identified and the have significant relationships toward employees’ performance in private companies with strong coefficient correlation statistically significant at 0.000. All sections of variables is also reliable for research because Cronbach Alphas coefficient is more than 0.60. All hypotheses and objectives are also accepted. So, from this study, the level of interaction and distraction give more influence to the employees’ performance. Future research can be done on the public sectors so that it can be compared with the findings of this study. In addition for a good study, the future research needs to adding more samples, variables, separate the level of interaction and level of distraction into different independent variables and use other sampling methods such as stratified sampling and simple random sampling in order to get better results for the study.